Feasibility of design broadband microstrip antenna using corporate feed / Muhammad A'dlan Abdulllah - Abdulllah, Muhammad A'dlan (2007)
This final project presents a design of a broadband microstrip antenna using corporate feed. The feed was used to achieve high directivity and to concentrate radiation power within a small geographic area. The antenna works from 9.4 GHz to 9.7 GHz. The simulation shows that the best value of VSWR was 1.034 and the return loss of -35.49 dB. The measurement results yield the lowest values of VSWR and the return loss of 1.2 dB and -22.80 dB respectively. The bandwidth that obtained from the antenna was 7.1 %. The antenna was designed and simulated using computer aided design (CAD),GENESYS and was measure by a Scalar Network Analyzer (SNA).The measurement results quite closely agree with the simulation results.